Randomised trial comparing propranolol with atenolol in immediate treatment of suspected myocardial infarction. Issue 6218 (29th March 1980) - Wilcox, R G; Roland, J M; Banks, D C; Hampton, J R; Mitchell, J R
Abstract : The value of beta-blockade for suspected acute myocardial infarction was assessed by determining the six-week and one-year mortality rates in patients started on propranolol, atenolol, or placebo immediately on entry to a coronary care unit. A total of 388 patients entered this double-blind, randomised study, and when analysed on the basis of the initial, intention-to-treat categories there was no significant difference between the three groups in respect of the mortality rate at one year. There was, however, a high withdrawal rate from the trial; the reasons for this illustrate problems of physician compliance and interpretation of data, which are common to all early-entry trials of haemodynamically active agents in acute myocardial infarction.